DILEMMAS OF INSTITUTIONAL DESIGN OF THE FORM OF GOVERNMENT FOR A SPLITTED SOCIETY - Попков, Д. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
The form of government is considered as an element of the system of political and institutional measures aimed at consolidating a divided society. Attention is drawn to the contradictory domestic experience of constituting the balance of powers between the president and parliament. The necessity of continuing professional scientific research in the context of overcoming the state of social division, which is diagnosed in Ukraine in the author's understanding of this concept after the events of Maidan 2014, is substantiated.The proposals concerning the form of government, which are developed within the framework of two main competing of power-sharing concepts: A. Leiphart's co-social democracy and D. Horowitz's integrative model, are analyzed. Weaknesses in the introduction of the presidential regime in the construction of a «grand coalition» of supporters of the consociational approach have been identified. The shortcomings of presidentialism are formulated and substantiated as recommendations of D. Horowitz's centripetal concept, and the connection of such warnings with the remarks on the presidential form of government, which were noted by H. Linz, is shown. D. Horowitz's arguments in defense of the presidential regime in the framework of his controversy with H. Linz with the definition of «strong» and «weak» arguments are analyzed.The solution of the dilemma is proposed from the angle of the question formulated by K. Popper: «How should we organize political institutions so that bad or incompetent rulers do not cause too much damage?». The conditions under which the institution of the president is really able to perform the positive function of an effective guarantor of social peace in a state with a heterogeneous society are determined: 1) election to this position according to the rule of maximum distributed support and 2) endowment of this position with the powers of the head of state only. The limits of authority and the main elements of the political influence of the head of state in the performance of the functions of the guarantor of the status quo of the social agreement formulated in the constitution on the rules of coexistence within the state of all ethnic, linguistic and confessional collective identities are outlined.